Digital transformation in self-assessment at Trade Union University - Phạm Thị Nga; Bùi Thị Thu Hà (Tạp chí Nghiên cứu Khoa học Công đoàn, 2023)
Digital transformation is an inevitable trend in the development process of society. Self-assessment is one of the urgent requirements of educational institutions in terms of integration into the national education system. Digital transformation in self-assessment of quality will become an indispensable requirement in today’s technology era.